Modular panel with wood and particleboards of sugarcane bagasse for cattle handling facilities - Sartori, Diogo de Lucca; Cravo, Julio Cesar Machado; Barrero, Nubia Garzon; Fiorelli, Juliano; Savastano Junior, Holmer; Nakanishi, Erika Yukari (Acta Scientiarum. Technology, 2015)
<!--[if gte mso 9]> 1024x768 <![endif]--> This work aimed at the construction and structural evaluation of modular panel with reforested wood, particleboards of sugarcane bagasse and a bi-component resin based on castor oil, for use in lateral closing for construction of crowding pens and chutes for cattle handling facilities. The quality of the particleboards was evaluated considering the requirements of NBR 14810 (ABNT, 2006) and A208.1 (ANSI, 1999). The structural performance of the modular panel was evaluated by the soft body impact testing. The results indicate that the particleboards have physical and mechanical properties that meet the minimum recommendations of the normative documents for structural use. The modular panel shows structural performance suitable to withstand impact loads equivalent to conditions of use, and can be used in cattle handling facilities. Â  <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->